Zimbabwe Elections - Shubin, Vladimir (Africana Studia, 2020)
The article is devoted to the history of elections for the years of independence of Zimbabwe. Particular attention is paid to the political crisis in this country in recent years, the results and consequences of the “hybrid” (presidential and parliamentary) elections held in 2018. The author concludes that the major changes in the political history of independent Zimbabwe be them positive or negative, took place outside the election process.